Oxytocin ameliorates bone cancer pain by suppressing toll-like receptor 4 and proinflammatory cytokines in rat spinal cord. (2nd April 2020) - Mou, Xiaping; Fang, Ji; Yang, An; Du, Gang
Abstract: Bone cancer pain is considered to be mechanistically unique compared with inflammatory or neuropathic pain states. Toll-like receptor 4 (TLR4) is a transmembrane receptor protein which has been reported to be involved in neuropathic pain. However, the role of TLR4 in bone cancer pain is still unclear. Therefore, the aim of this study is to investigate the hypothesis that oxytocin may ameliorate bone cancer pain by suppressing TLR4 in spinal cord. Behavioral analysis and molecular biological experiments were carried out. Our data demonstrated that intrathecally delivery of oxytocin significantly ameliorated the mechanical allodynia and thermal hyperalgesia in bone cancer pain rats. Moreover, oxytocin suppressed the up-regulation of TLR4 and proinflammatory cytokines TNFα and IL-1β in spinal cord of bone cancer pain rats. Therefore, we concluded that intrathecal administration of oxytocin relieves bone cancer pain by suppressing the up-regulation of TLR4, TNFα and IL-1β in spinal cord. Oxytocin possesses analgesic efficacy against bone cancer pain and deserves further to confirm its effectiveness in clinically relevant of cancer pain.